Extracto de paico (chenopodium ambrosioides) y su efecto antihelmíntico en terneros - Arroyo Cedeño, Jonathan Xavier (2018)
Parasitosis is one of the main causes of loss of livestock productivity in Ecuador, which makes it necessary to establish alternative treatments to chemicals. The objective of this thesis was to evaluate the effect of the paico (Chenopodium ambrosioides) as antiparasitic and the causal toxicity. Twenty-one zebu cross calves were used, which received in a single application three doses of paico (0.15, 0.20, 0.25 ml), one group diluted in water and another in glycerin, and control abendazole 0.10 ml / kg (Abendazol 25%, Servinsumos®, CA Ecuador). The variables were considered: count of helminth eggs before and after application, effectiveness of the products, and toxicity of the products and cost of the treatments. All data were analyzed by ADEVA. No significant differences were found in the use of paico on the parasitic load (P> 0.05), however significant differences were found (P <0.0011) in the blood count in the group of animals treated with 0.20 ml of paico in glycerin, with respect to the control (31.67 and 39.00%, respectively). Regarding the effectiveness of the products, only one numerical difference was found (P = 0.55) of the group of animals treated with abendazole (93.98%), with respect to the other treatments (<40.00%). On the other hand, no significant differences were found among the other variables studied (P> 0.05). It is concluded that the treatments with paico extract diluted in water or in glycerin are not efficient to achieve a correct parasitic control, despite not finding a toxic effect of the product.